Faktor-Faktor yang Berhubungan dengan Kepatuhan Perawat dalam Melaksanakan Standar Asuhan Keperawatan - Febi Gabriela Sabanari; Irma M. Yahya; Norman Alfiat Talibo (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
The implementation of nursing care standards is the provision of nursing care that based on solving patient's problems. Several factors that are believed to influence nurses' compliance in implementing nursing care standards are including education, work experience, and motivation. The purpose of this study is to determine the factors related to nurses' compliance in implementing nursing care standards at the 3rd grade hospital of bhayangkara in Manado. The results of the study showed that there is no relationship between education factors and nurse compliance point p (0.630), this point p is bigger than the point ɑ = 0.05. There is a relationship between work experience factors and nurse compliance p = 0.004, this point p is smaller than the point ɑ = 0.05. There is a relationship between motivational factors and nurse compliance in implementing nursing care standards p = 0.000, this point p is smaller than the point ɑ = 0.05. The conclusion in this study is that almost all of the respondents have a high motivation in implementing nursing care standards at the 3rd grade hospital of bhayangkara in Manado. In expecting that this study could be an input to increase the nurse compliance in implementing nursing care standards.